From immigrants to (non-)citizens: political economy of naturalisations in Latvia - Artjoms Ivļevs; Roswitha M. King (IZA Journal of Migration, 2012)
We study the determinants of the willingness to acquire citizenship of Latvia by 'non-citizens' - the former Soviet migrants and their descendants born on the territory of Latvia. The country of Latvia serves as an instructive laboratory for the analysis of naturalisations: due to the centrally planned nature of its 1945-1991 immigration flows, we can exclude the possibility that migrants came with an intention to acquire host country citizenship. Using data from a 2007 survey of 624 former and current 'non-citizens', we find that the elderly, males, single, and those with poor knowledge of the State language are less willing to naturalise. Prospective emigrants are more likely to have naturalised recently in preparation for partaking in the wider EU labour market - a right that citizenship of EU member Latvia conveys. Instrumental variable analysis suggests that low level of education is an obstacle for acquiring citizenship, while higher unemployment rate and lower share of non-citizens at a respondent's place of residence contributes to early naturalisations.
Keywords: F22; J15; J61; 330; naturalisation; Latvia; non-citizens; migrants